STRATEGI GURU PAUD DALAM MENGINTEGRASIKAN NILAI-NILAI KEISLAMAN PADA KEGIATAN BELAJAR - Syahid, Ishaq; Mustaqim, Ismail; Rohman, Syaiful (WALADI, 2025)
This ethnographic qualitative study aims to describe the strategies of Early Childhood Education (PAUD) teachers at Al-Hidayah Kindergarten, Bangkalan, in integrating Islamic values into learning activities. Data were collected through participant observation, in-depth interviews, and document studies, then analyzed interactively using the Miles & Huberman model. The findings reveal three main results: (1) Thematic-integrative planning strategies using a Value Matrix in the Weekly Activity Plan (RKH) through a collaborative process; (2) Implementation through routine habituation, exemplary behavior (uswah hasanah), utilization of teachable moments, and positive reinforcement across various play centers; (3) The main supporting factors are teacher commitment and exemplary behavior, school leadership, and partnerships with parents, while limitations in facilities are overcome through teacher creativity. The study concludes that the effectiveness of value integration is determined primarily by the teacher's capacity as a living curriculum through micro and contextual interactions, rather than by the adequacy of facilities. This research contributes to developing a practical model of value education based on local wisdom in early childhood education.